Asymmetric aminohydroxylation route to (+)-L-733,060 - Kandula, Subba Rao V.; Kumar, Pradeep (Tetrahedron-Asymmetry, 2005)
An enantioselective synthesis of (+)-L-733,060 starting from cinnamic acid using Sharpless asymmetric aminohydroxylation and Wittig reactions as the key steps is described. (c) 2005 Elsevier Ltd. All rights reserved.